Semi automatic transmission using motor wiper / Mohd Nazari Mohd Dakir, Mohd Nazrol Mokhtar and Ahmad Zaki Abdul Latib - Mohd Dakir, Mohd Nazari; Mokhtar, Mohd Nazrol; Abdul Latib, Ahmad Zaki (2001)
The use of motor wiper in a vehicle is a must especially in the rain condition, but the function of motor wiper can be range to other application. The need to study the properties and characteristic of motor wiper has become a very important subject in order to get the new usage of this type of technology. This semi-automatic transmission project using motor wiper is because it characteristic that move in 2 steps. Firstly it moves forward or in one direction and then it will move back to their original place. The only motor that operates in this characteristic in the vehicle is motor wiper. The selection however included the motor wiper can easily get from junkyard shop or "kedai potong kereta" in affordable price. There are so many model in variable size.